CRTAM Protects Against Intestinal Dysbiosis During Pathogenic Parasitic Infection by Enabling Th17 Maturation - Cervantes-Barragan, Luisa; Cortez, Victor S.; Wang, Qiuling; McDonald, Keely G.; Chai, Jiani N.; Di Luccia, Blanda; Gilfillan, Susan; Hsieh, Chyi-Song; Newberry, Rodney D.; Sibley, L. David; Colonna, Marco (Frontiers in Immunology, 2019)
The gastrointestinal tract hosts the largest collection of commensal microbes in the body. Infections at this site can cause significant perturbations in the microbiota, known as dysbiosis, that facilitate the expansion of pathobionts, and can elicit inappropriate immune responses that impair the intestinal barrier function. Dysbiosis typically occurs during intestinal infection with Toxoplasma gondii. Host resistance to T. gondii depends on a potent Th1 response. In addition, a Th17 response is also elicited. How Th17 cells contribute to the host response to T. gondii remains unclear. Here we show that Class I-restricted T cell-associated molecule (CRTAM) expression on T cells is required for an optimal IL-17 production during T. gondii infection. Moreover, that the lack of IL-17, results in increased immunopathology caused by an impaired antimicrobial peptide production and bacterial translocation from the intestinal lumen to the mesenteric lymph nodes and spleen.